Analysis Of The Influence Of Corporate Governance And Enterprise Risk Management Coso On Firm Performance With The Mediation Role Of Operational Efficiency - kaban, ekin; Muhammad , Saifi; Atmanto , Dwi; imamah, Nur (The International Journal of Accounting and Business Society, 2025)
Purpose — This study investigates the effects of Enterprise Risk Management (ERM) and Good Corporate Governance (GCG) on firm performance, with operational efficiency serving as a mediating variable, using secondary data from KBMI 3 banks in Indonesia over five years Design/methodology/approach — The analysis, conducted through Partial Least Squares Structural Equation Modeling (PLS-SEM), shows that ERM has a significant positive effect on operational efficiency (β = 0.29, p = 0.01) and firm performance (β = 0.27, p < 0.05). At the same time, GCG does not exhibit a significant direct impact on either outcome. Both ERM and GCG significantly influence operational efficiency. Still, their direct effect on firm performance is not statistically significant (β = 0.03, p = 0.40), suggesting the presence of indirect pathways and external moderating factors. Findings — These results provide empirical support for the role of operational efficiency as a partial mediator between ERM and firm performance, contributing to a deeper understanding of performance dynamics in the Indonesian banking sector. Practical implications — The study advances existing literature by embedding efficiency into the governance–risk–performance nexus. It offers useful insights for banking practitioners and regulators to enhance risk alignment, internal process integration, and sustainable performance management. Originality/value — The study advances existing literature by embedding operational efficiency into the governance–risk–performance nexus. It provides empirical support for the role of operational efficiency as a partial mediator between ERM and firm performance, contributing to a deeper understanding of performance dynamics in the Indonesian banking sector (KBMI 3 banks). It offers practical insights for banking practitioners and regulators to enhance risk alignment, internal process integration, and sustainable performance management.